COLLABORATIVE GOVERNANCE STRATEGY IN THE IMPLEMENTATION OF PLANNING AND DEVELOPMENT DELIBERATIONS IN TOJO UNA-UNA REGENCY, INDONESIA (Lex localis - Journal of Local Self-Government, 2025)
This study examines the strategy of collaborative governance in the implementation of the Development Planning Consultation (Musrenbang) in Tojo Una-Una Regency, Indonesia. The research addresses the problem of limited effectiveness of participatory planning mechanisms due to disparities in community involvement, technical constraints, budgetary limitations, and coordination challenges among stakeholders. The objective is to analyze the current implementation of Musrenbang, identify the strategic position of the region, and formulate appropriate strategies to strengthen collaborative governance in regional development. The study employs a qualitative case study approach, utilizing in-depth interviews with government, legislative, and community representatives, focus group discussions, participant observation, and document analysis. Data were analyzed through SWOT methodology combined with IFAS and EFAS matrices. Findings indicate that Tojo Una-Una Regency is in a strong strategic position (IFAS: 2.99; EFAS: 2.94), placing it in Quadrant I (Growth Strategy). Strengths include a well-established institutional structure, active participation, transparency, and successful programs such as the Clean Water Access Improvement initiative. However, weaknesses include unequal participation, limited technical skills, budget constraints, and suboptimal coordination. The greatest opportunities lie in digital technology adoption, capacity building, optimization of local resources, and stronger stakeholder networks. The study concludes that Musrenbang can become an effective instrument of collaborative governance if adapted as a genuinely inclusive platform integrating community aspirations with government priorities. Recommended strategies focus on digital participation, strengthening community capacity, replicating successful models, and institutionalizing stakeholder partnerships to achieve sustainable and inclusive development.